Efficient demethylation of aromatic methyl ethers with HCl in water. Issue 5 (26th February 2021) - Bomon, Jeroen; Bal, Mathias; Achar, Tapas Kumar; Sergeyev, Sergey; Wu, Xian; Wambacq, Ben; Lemière, Filip; Sels, Bert F.; Maes, Bert U. W.
Abstract : A method for the cleavage of aryl alkyl ethers is presented, involving hot pressurized water and catalytic mineral acid. The protocol is applicable on a variety of (biorenewable) substrates, not requiring mass-intensive work-up. Abstract : A green, efficient and cheap demethylation reaction of aromatic methyl ethers with mineral acid (HCl or H2 SO4 ) as a catalyst in high temperature pressurized water provided the corresponding aromatic alcohols (phenols, catechols, pyrogallols) in high yield. 4-Propylguaiacol was chosen as a model, given the various applications of the 4-propylcatechol reaction product. This demethylation reaction could be easily scaled and biorenewable 4-propylguaiacol from wood and clove oil could also be applied as a feedstock. Greenness of the developed method versus state-of-the-art demethylation reactions was assessed by performing a quantitative and qualitative Green Metrics analysis. Versatility of the method was shown on a variety of aromatic methyl ethers containing (biorenewable) substrates, yielding up to 99% of the corresponding aromatic alcohols, in most cases just requiring simple extraction as work-up.